CP-076 Post-marketing active pharmacovigilance in a central hospital. (24th March 2015) - Parola, A; Chambel, P; Farinha, H; Falcão, F
Abstract : Background: Hospital settings are of great value in collecting pharmacovigilance data. Introduction of innovative drugs in hospital settings raises safety concerns, but allows the study of these drugs' safety profile in real life. Hospital Pharmacists may play an important role in these activities. Purpose: To assess the adverse drug reactions (ADRs) profile of 3 recently marketed drugs, introduced in a central hospital. Material and methods: As part of our active pharmacovigilance programme, a prospective, observational study was carried out on patients receiving fingolimod, telaprevir or boceprevir, between January 2012 and September 2014. ADRs encountered were analysed for age, sex, ADR category and seriousness. Severe, unexpected, frequent, uncommon or rare ADRs were reported to the National Pharmacovigilance System (NPS). Results: A total of 41 patients were enrolled, median age 44 years, 41% male and 59% female. 253 ADRs were observed In 37 patients. 28 reports regarding 173 ADRs were sent to NPS. As defined by the Naranjo causality assessment of ADRs, 90 were considered to have a possible, 53 a probable, and 1 a definitive causal relation with the studied drugs (NPS response rate: 83%). Most frequently observed ADRs (n = 159) in boceprevir/telaprevir regimens were: anaemia (70%), thrombocytopenia (78%), and pruritus (57%). Regarding fingolimod (n = 94), most frequently observed ADRs were: lymphopenia (60%) and paresthesia (24%); initial dose ECG monitoring was performed in all patients, but symptomatic bradycardia was seen in only two cases, without stopping treatment. Severe ADRs occurred in 5%, and moderate ADRs in 16% of the patients. Some patients had to stop taking the drug in all drugs studied. Conclusion: ADRs were common in patients taking the triple drug regimen for hepatitis C, while fingolimod was relatively well tolerated, which is in line with international literature data. Frequency and severity of ADRs can be managed by laboratory and clinical vigilance and instituting appropriate measures. References and/or Acknowledgements: No conflict of interest.